Peningkatan Produktivitas Ayam Petelur Melalui Pemberian Ekstrak Etanol Daun Kemangi (INCREASED LAYING HENS PRODUCTIVITY THROUGH THE ADMINISTRATION OF ETHANOL EXTRACT OF KEMANGI LEAVES) - ., Andriyanto; Arif, Ridi; Miftahurrohman, Mohammad; Rahayu, Yayuk Sri; Chandra, Erli; Fitrianingrum, Alifiana; Anggraeni, Risna; Pristihadi, Diah Nugrahani; Mustika, Aulia Andi; Manalu, Wasmen (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
Empirically, kemangi leaves reported to increase health quality in human and livestock. Thepreliminary study was designed to explore the potency of ethanol extract of kemangi leaves to increaselaying hens performance. Sixteen laying hens (pullet) were divided into 4 groups and repeated 4 times.Control group was laying hen administered aquadest orally, treated group was laying hen administeredextract of kemangi leaves orally at a dose of 1, 2, and 3 mg/kg BW, respectively. Every day, the experimentallaying hens were fed for 3 times and drinking water was provided ad libitum. Variables observed were thenumber of eggs, egg weight, time of first laying, egg laying intervals, egg quality ( water content, crudeprotein, and crude fat), and liver function (SGPT and SGOT values) . Results of this research showed thatadministration of kemangi leaves extract at a dose of 3 mg/kg BW significantly increased the number ofegg production and egg weight (p<0.05). Time of first laying and laying interval did not show any significantdifference among treatments. Examination of moisture, crude protein, and crude fat content of the eggindicated that the administration of kemangi leaves extract did not affect egg quality. Extract of kemangileaves decreased SGPT and SGOT values that indicated improvement of liver function. It was concludedthat administration of ethanol extract of kemangi leaves could increase laying hens productivity byimprovement of liver function that is critical in vitellogenesis.
Keywords: extract ethanol kemangi leaves, productivity, liver function, laying hens